The Threat of Punishment Under Article 412 of Law Number 1 of 2023 Con-cerning the New Criminal Code Against Cohabitants - Folce Elden Palyama (IHSA Institute, 2026)
The phenomenon of cohabitation, namely living together as a married couple outside of a formal marriage, is increasingly widespread and has sparked debate from a legal and social perspective in Indonesia. Law Number 1 of 2023 concerning the Criminal Code (KUHPidana), through Article 412, regulates criminal penalties for cohabitants, with the aim of upholding social norms and community morals. This study uses a juridical normative method to analyze the provisions of Article 412, its legal implications, and challenges in law enforcement. The results of the study indicate that the article criminalizes cohabitation with a maximum prison sentence of six months or a fine, but has given rise to multiple interpretations and controversy regarding the definition, reporting, and proportionality of the sentence. Furthermore, the application of this article has the potential to create social stigma and human rights violations, so a balanced approach is needed between enforcing norms and protecting individual rights. The study recommends improving regulations to avoid legal uncertainty and ensure fairness in law enforcement against cohabitation amidst the dynamics of modern Indonesian society